1995
DOI: 10.1021/bi00051a017
|View full text |Cite
|
Sign up to set email alerts
|

Yeast protein farnesyltransferase: steady-state kinetic studies of substrate binding

Abstract: Protein farnesyltransferase (PFTase) catalyzes the alkylation of cysteine in C-terminal CaaX sequences of a variety of proteins, including Ras, nuclear lamins, large G-proteins, and phosphodiesterases, by farnesyl diphosphate (FPP). These modifications enhance the ability of the proteins to associate with membranes and are essential for their respective functions. The binding mechanism for yeast PFTase was deduced from a combination of steady-state kinetic and equilibrium studies. Rates for prenylation were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
56
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 30 publications
7
56
0
Order By: Relevance
“…The reaction mechanism thus appears identical to that of FPTase (17). On the other hand, the yeast enzymes yGGPTase I and yFPTase have been reported to proceed through an ordered Bi Bi mechanism (18,19). Interestingly, and in contrast to FPTase, GGPTase I does not require Mg 2ϩ for GGPP binding or catalysis.…”
mentioning
confidence: 76%
“…The reaction mechanism thus appears identical to that of FPTase (17). On the other hand, the yeast enzymes yGGPTase I and yFPTase have been reported to proceed through an ordered Bi Bi mechanism (18,19). Interestingly, and in contrast to FPTase, GGPTase I does not require Mg 2ϩ for GGPP binding or catalysis.…”
mentioning
confidence: 76%
“…Original studies suggested that the prenylation reaction catalyzed by farnesyl transferase or GGTase I proceeds via a random sequential mechanism by which the enzyme can bind the protein and lipid substrates independently [8,9]. However, recent studies with human and yeast farnesyl transferase supported an ordered addition of substrates [10,11].In contrast with other known prenyl transferases, RabGGTase does not recognize its substrate directly but exerts its function in concert with another protein termed REP (Rab escort protein) [12,13]. Two known mammalian proteins, Eur.…”
mentioning
confidence: 99%
“…Original studies suggested that the prenylation reaction catalyzed by farnesyl transferase or GGTase I proceeds via a random sequential mechanism by which the enzyme can bind the protein and lipid substrates independently [8,9]. However, recent studies with human and yeast farnesyl transferase supported an ordered addition of substrates [10,11].…”
mentioning
confidence: 99%
“…Steady-state kinetic analyses of PFT and PGGT-I show that both enzymes can operate by a random sequential mechanism in which either prenyl donor or acceptor binds first to the enzyme followed by binding of the other substrate to form a ternary complex that goes on to products. However, operationally, both enzymes show a strong tendency to bind prenyl pyrophosphate first (25)(26)(27)(28). Both PFT and PGGT-I have been shown to tightly bind both FPP and GGPP (12,29,30).…”
mentioning
confidence: 99%